Identification of a novel, pathogenic CREBBP variant in a patient with Menke-Hennekam syndrome: a Case Report - Anastasiou, Anna Μaria; Aristidou, Constantia; Theodosiou, Athina; Kousoulidou, Ludmila; Papaevripidou, Ioannis; Alexandrou, Angelos; Evangelidou, Paola; Sismani, Carolina; Tanteles, George A.; Sanoudou, Despina; Eliopoulos, Aristides G. (Frontiers in Genetics, 2025)
Menke-Hennekam syndrome (MKHK) is a recently described rare autosomal dominant disorder caused by loss-of-function variants in exon 30 or 31 of CREBBP (CREB-binding protein) or EP300 genes. These genes encode transcriptional coactivators with a key role in chromatin remodeling and regulation of gene expression. Herein, we report the identification and characterization of a novel missense variant in CREBBP, NM_004380.3:c.5368T>C p.(Cys1790Arg), in a 4-year-old male. The clinical presentation of the patient included global developmental delay, intellectual disability, growth retardation, and distinct craniofacial dysmorphisms, resembling known MKHK subtypes, but also exhibiting less common or unique features such as excessive palmar skin and the absence of recurrent infections and autism spectrum behaviors. Genetic analysis via trio-based clinical exome sequencing confirmed the de novo origin of the CREBBP variant, which was classified as pathogenic based on ACGS guidelines 2020. Structural modeling predicted that the NP_004371.2:p.(Cys1790Arg) substitution may disrupt the tertiary structure of the CBP TAZ2 domain (amino acids 1772-1840) when interacting with STAT1 but not with adenovirus E1A, potentially affecting transcription factor binding and disease phenotype. The findings contribute to the evolving classification of MKHK subtypes and to deciphering the complexity of genotype-phenotype relationships in MKHK.